Food safety knowledge and hygiene practices among veterinary medicine students at Trakia University, Bulgaria - Deyan Stratev; Olumide A. Odeyemi; Alexander Pavlov; Ralica Kyuchukova; Foad Fatehi; Florence A. Bamidele (Elsevier, 2017)
The results from the first survey on food safety knowledge, attitudes and hygiene practices (KAP) among veterinary medicine students in Bulgaria are reported in this study. It was designed and conducted from September to December 2015 using structured questionnaires on food safety knowledge, attitudes and practices. Data were collected from 100 undergraduate veterinary medicine students from the Trakia University, Bulgaria. It was observed that the age and the gender did not affect food safety knowledge, attitudes and practices. There was no significant difference (p > 0.05) on food safety knowledge and practices among students based on the years of study. A high level of food safety knowledge was observed among the participants (85.06%), however, the practice of food safety was above average (65.28%) while attitude toward food safety was high (70%). Although there was a significant awareness of food safety knowledge among respondents, there is a need for improvement on food safety practices, interventions on food safety and foodborne diseases. Keywords: Food safety, Awareness, Foodborne infections, Hygiene, Consumers